Laser Treatment of Cutaneous Vascular Anomalies and Pigmented Lesions - Mishra, Mithilesh J.; Alani, Hashim (Indian Journal of Plastic Surgery, 1983)
A total of 232 patients with portwine stains and totoos were examined from 1978 to 1982. One-hundren-seventeen patients were subjected to the test dose of laser to evaluate the initial result and applicability for further treatment. Twenty-five patients were discarded for treatment. A total of 92 patients, 48 patients with hemangiomas, 32 with tattoos, 10 with nevi and 2 patients with multiple warts, were treated with excellent results.